Factors Influencing Preservice Teachers' Intention to Use Technology: TPACK, Teacher Self efficacy, and Technology Acceptance Model - Joo, Young Ju; Park, Sunyoung; Lim, Eugene (Educational Technology ＆ Society, 2018)
This study aimed to investigate structural relationships between TPACK, teacher self-efficacy, perceived ease of use, and perceived usefulness for preservice teachers who intend to use technology, based on the Technology Acceptance Model (TAM). A total of 296 responses from the College of Education from three Korean universities were analyzed by employing the structural equation modeling methods. The results indicated that preservice teachers' TPACK significantly affected teacher self-efficacy and perceived ease of using technology. The teachers' TPACK also positively influenced their perceived ease of using technology and perceived usefulness of technology in the classroom. Finally, teacher self-efficacy, perceived ease of use, and perceived usefulness of using technology affected teachers' intention to use technology. However, TPACK did not directly affect their intention to use technology. Based on the findings, we discuss implications and suggest future research directions for preservice teachers' intention to use technology.